Candida glabrata およびその他のCandida属の抗真菌薬感受性におけるアゾールトランスポーター阻害薬の効果 - 永吉, 洋介 (Public Library of Science, 2018)
Nagasaki University (長崎大学) 博士(医学) The pathogenic fungus Candida glabrata is often resistant to azole antifungal agents. Drug efflux through azole transporters, such as Cdr1 and Cdr2, is a key mechanism of azole resistance and these genes are under the control of the transcription factor Pdr1. Recently, the monoamine oxidase A (MAO-A) inhibitor clorgyline was shown to inhibit the azole efflux pumps, leading to increased azole susceptibility in C. glabrata. In the present study, we have evaluated the effects of clorgyline on susceptibility of C. glabrata to not only azoles, but also to micafungin and amphotericin B, using wild-type and several mutant strains. The addition of clorgyline to the culture media increased fluconazole susceptibility of a C. glabrata wild-type strain, whereas micafungin and amphotericin B susceptibilities were markedly decreased. These phenomena were also observed in other medically important Candida species, including Candida albicans, Candida parapsilosis, Candida tropicalis, and Candida krusei. Expression levels of CDR1, CDR2 and PDR1 mRNAs and an amount of Cdr1 protein in the C. glabrata wild-type strain were highly increased in response to the treatment with clorgyline. However, loss of Cdr1, Cdr2, Pdr1, and a putative clorgyline target (Fms1), which is an ortholog of human MAO-A, or overexpression of CDR1 did not affect the decreased susceptibility to micafungin and amphotericin B in the presence of clorgyline. The presence of other azole efflux pump inhibitors including milbemycin A4 oxime and carbonyl cyanide 3-chlorophenylhydrazone also decreased micafungin susceptibility in C. glabrata wild-type, Δcdr1, Δcdr2, and Δpdr1 strains. These findings suggest that azole efflux pump inhibitors increase azole susceptibility but concurrently induce decreased susceptibility to other classes of antifungals independent of azole transporter functions. 長崎大学学位論文 学位記番号:博(医歯薬)甲第1027号 学位授与年月日:平成30年3月7日 Author: Yohsuke Nagayoshi, Taiga Miyazaki, Shintaro Shimamura, Hironobu Nakayama, Asuka ...